DEZVOLTAREA ÎNVĂŢĂMÂNTULUI SUPERIOR DIN REPUBLICA MOLDOVA - USM ADMIN (Moldova State University, 2007)
The development of the Moldovan state, of civil society and economic reform are impossible without solving problems connected with educational development, especially, higher education, according to nowadays requirements. Higher education in Republic of Moldova has a strategic mission for development and maintaining of competent human resources, who is able to assure a lasting development of the society. This mission is accomplished by assuring the quality of educational and professional development, free research, university autonomy, and permanent connection to the needs of labor market.